Comparison of Different Herbal Additives on Immune Response and Growth Performance of Broiler Chickens - S. Masoud-Moghaddam; J. Mehrzad; A. H. Alizadeh-Ghamsari; R. Bahari Kashani; J. Saeidi (Tropical Animal Science Journal, 2021)
This experiment was conducted to compare the effects of four commercial herbal additives (Noviherb®, Bioessence®, Biostrong®, and Novigrow®), and a commercial antibiotic (virginiamycin) on growth performance, carcass yield, visceral organs weight, thyroid hormones, and humoral immune responses of broiler chickens. Nine hundred day-old Ross 308 male broiler chicks were reared in litter-covered floor cages and distributed into five experimental groups with six replicates of 30 birds. Five dietary treatments tested were diets supplemented with Noviherb®, Bioessence®, Biostrong® (each of them 100g/ton of diet), Novigrow® (1000g/ton of diet), and virginiamycin (100g/ton of diet) as a positive control. Feed intake, body weight, mortality, feed conversion ratio, European broiler index, and feed cost per kilogram of body weight were measured during the experiment. Antibody titers against sheep red blood cells (SRBC), immunoglobulin G, immunoglobulin M, and plasma concentrations of thyroxine (T4) and triiodothyronine (T3) were evaluated at the age of 42 days. Then, four birds per replicate were killed to determine the relative weight of carcass and organs. The GLM procedures of SAS software and Duncan’s multiple range test were applied to analyze data in a completely randomized design with five treatments and six replicates of 30 birds per each. The effects of herbal additives on productive traits feed cost per kilogram of body weight and relative weight of organs were not significant in comparison with antibiotic treatment. Dietary inclusion of Noviherb®, Biostrong®, and Novigrow® significantly decreased feed cost per kilogram of carcass compared with Bioessence® or antibiotic treatments (p<0.05). The titers of IgG in Noviherb® and virginiamycin were significantly higher (p<0.05) than in Biostrong® and Novigrow® fed groups. The plasma concentration of triiodothyronine was significantly decreased (p<0.05) by dietary inclusion of Noviherb® and Novigrow® compared to the antibiotic. In conclusion, all the evaluated herbal additives could act as a substitute for the growth-promoting antibiotic.